Book review: Adrian Athique and Vibodh Parthasarathi (Eds). 2020. Platform Capitalism in India. (December 2022) - Guha, Suryansu
Adrian Athique and Vibodh Parthasarathi (Eds). 2020. Platform Capitalism in India . Springer International Publishing, 331 pages.